2016
DOI: 10.1038/jid.2015.381
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Tyrosine Kinase Mediates EGFR Signaling to Regulate Keratinocyte Terminal Differentiation

Abstract: Spleen tyrosine kinase (Syk), a non-receptor tyrosine kinase, was initially identified as a crucial regulator in proximal immunoreceptor signaling. Additional studies have revealed its pleiotropic roles, and drugs targeting Syk are under development for inflammatory diseases. Syk expression in the skin has been detected, but its functions in the skin are still unknown. Here, we found that Syk phosphorylation and expression in primary human keratinocytes decrease gradually along with terminal differentiation. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…A literature search revealed that approximately one third of genes that carried non-synonymous mutations had been reported in the context of skin physiology and keratinocyte proliferation [3441]. Activation of CDK2 in mouse epidermis reportedly induces keratinocyte proliferation, however did not affect skin tumor development [42, 43] Also SYK has been shown to act as a negative regulator in epidermal keratinocyte differentiation and is also involved in EGFR signaling, which may contribute to its regulatory role in keratinocyte terminal differentiation [44]. NEDD4 is involved in the ΔNp63α-mediated suppression of nuclear PTEN in basal layer keratinocytes, whereas nuclear PTEN inhibits cell proliferation and mice with a keratinocyte-specific null mutation of Pten reportedly exhibit epidermal hyperplasia and hyperkeratosis [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search revealed that approximately one third of genes that carried non-synonymous mutations had been reported in the context of skin physiology and keratinocyte proliferation [3441]. Activation of CDK2 in mouse epidermis reportedly induces keratinocyte proliferation, however did not affect skin tumor development [42, 43] Also SYK has been shown to act as a negative regulator in epidermal keratinocyte differentiation and is also involved in EGFR signaling, which may contribute to its regulatory role in keratinocyte terminal differentiation [44]. NEDD4 is involved in the ΔNp63α-mediated suppression of nuclear PTEN in basal layer keratinocytes, whereas nuclear PTEN inhibits cell proliferation and mice with a keratinocyte-specific null mutation of Pten reportedly exhibit epidermal hyperplasia and hyperkeratosis [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Using the meta-analysis derived atopic dermatitis transcriptome (MADAD) [26] as a reference core AD transcriptome, Pavel et al presented data which supported the usage of dual JAK/SYK inhibition in AD by showing a dose-dependent improvement of the transcriptomic profile. The rational of this approach refers to the inhibition of T cell polarization by JAK inhibition [239] as well as improvement of the terminal epidermal differentiation by SYK inhibitors [240]. Additionally, IL31 expression was reduced more efficiently by the dual inhibition approach than that seen in dupilumab treatment.…”
Section: Prognostics and Treatmentmentioning
confidence: 99%
“…SYK is involved in several cytokine signalling pathways, including the Th17 pathway . It induces the production of CCL20, which attracts Th17 cells to the skin . SYK also acts as a negative regulator of keratinocyte differentiation, and gradually decreases during the terminal differentiation process owing to a cross‐regulation with epidermal growth factor receptor .…”
Section: Discussionmentioning
confidence: 99%
“…It induces the production of CCL20, which attracts Th17 cells to the skin . SYK also acts as a negative regulator of keratinocyte differentiation, and gradually decreases during the terminal differentiation process owing to a cross‐regulation with epidermal growth factor receptor . In addition, SYK is involved in the survival, proliferation, and activation of B lymphocytes and in differentiation of dendritic cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation